Applying the constraints-led approach to facilitate exploratory learning of the volleyball serve - Moy, B.; Renshaw, I.; Gorman, A. D. (Journal of Sports Sciences, 2024)
Exploration is an important feature for successfully learning motor skills. However, game rules such as one attempt to serve in volleyball could discourage exploration due to an individual`s fear of making a mistake and forfeiting a point. The constraints-led approach is a coaching methodology that encourages exploration by selectively manipulating task constraints such as rules. Therefore, the aim of this study was to examine whether the addition of the task constraint of a second serve would encourage volleyball players to use their first serve to explore their action capabilities. Forty male high school students competed in two volleyball games; a regulation (single serve) game and a modified (2-serve) game. Participants reported that having a second chance at serving allowed them to feel more confident and relaxed which facilitated the exploration of their serving capability. In the 2-serve game, participants attempted a more powerful (M = 60.3 km/hr), and complex (M = 44.5% jump topspin serves) first serve, compared to the regulation game (M = 55.6 km/hr; M = 25.2% jump topspin serves). Findings suggest that to facilitate learning of motor skills, it is important to manipulate the practice environment using task constraints to address the factors that restrict exploration.